COMPARATIVE STUDY OF THE QUALITY OF BOILED FISH PRESTO JELAWAT (Leptobarbus hoeveni) WITH PACKAGING METHODS VACUUM AND NON VACUUM DURING STORAGE - Rachmat, Dedy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aims to study the quality of boiled fish presto jelawat with different packaging for low temperature storage seen from organoleptic value, moisture content, TVN (Total Volatile Nitrogen), Fungi and bacteria psikrofilik. The method used is a comparative study (comparative experiment) of the quality of boiled presto fish jelawat vacuum (V) and boiled presto non vacuum (NV) conducted cold storage at a temperature of Â± 5 C with a time interval of observation 0, 10, 20, 30 days with each treatment were conducted three times. Quality research results presto boiled fish jelawat with vacuum packaging method is the best treatment. The results of the showed the water content of vacuum packaging 56,13% and packaging non vacuum 59,99%. TVN analysis showed vacuum packaging 21,76 mgN/100g and packaging non vacuum 24,44 mgN/100g. Psikrofilik bacterial analysis indicates vacuum packaging 3,43x10Â² cfu/mL and non vacuum packaging 4,67x10âµ cfu/mLKeywords : Pindang Presto, Vacuum and Non Vacuum, Fish Jelawat